Determinants of objective and subjective auditory disability in patients with normal hearing - Saunders, Gabrielle H. (1989)
A proportion of individuals consulting audiology clinics complain of difficulties discriminating speech in noisy environments but have clinically 'normal' hearing, do not have signs of middle ear pathology, nor any other obvious basis for their complaints. The syndrome was named 'Obscure Auditory Dysfunction (OAD)'. Following a small scale study, a Special Investigative Clinic was started to investigate factors underlying OAD. Patients' performance on psychoacoustic, central/cognitive and personality-related tests was compared with the performance of matched controls. Results showed OAD to be a multifactorial syndrome. Patients have a genuine performance deficit for discrimination of speech-in-noise, influenced by a combination of psychoacoustic and central/cognitive deficits. Patients' relatively minor performance deficit did not completely explain their reported disability and handicap; this was mainly influenced by their underestimating their hearing ability. Anxiety-related factors and a history of otological disorder were found to underlie the seeking of medical attention. Based on these results, a clinical package was devised to enable diagnosis and understanding of OAD in individuals consulting in the clinic. The parallels between OAD and another syndrome without obvious organic pathology (women complaining of lower abdominal pain) were investigated. A double dissociation between personality-related factors and psychoacoustic/cognitive factors was demonstrated. It was concluded that personality factors should be considered when dealing with individuals seeking medical advice for minor organic pathology, but that such individuals should not simply be dismissed as being neurotic. Finally, correlational analyses using the combined data of all subjects, were carried out to investigate relationships between self-rated auditory disability/handicap, psychoacoustic, central/cognitive and personality-related variables. Self-rated disability/handicap were found to correlate best with performance on a test of speech-in-noise, less well with subtle auditory function but not with pure tone sensitivity. Cognitive function also correlated with reported disability/handicap, as did anxiety level and otological history. It was concluded that performance measures could be used to validate reports of disability/handicap, but that personality factors should be taken into account when interpreting such reports. Performance on a speech-in-noise test correlated with psychoacoustic and central/cognitive functions, but not with personality factors. It was concluded that minor sensory dysfunction can be reflected in a sensitive performance test but that performance is not affected by 'normal' personality traits.